Collection of location data in criminal proceedings – European (the EU and Strasbourg) standards - Dominika Czerniak (Revista Brasileira de Direito Processual Penal, 2021)
This article deals with the problem of collecting, retaining and processing location data for use in criminal proceedings. The collection of location data is an interference with the right to privacy (the Article 8 of the ECHR, the Article 7 of the Charter). However, such interference is permissible if it pursues the aims indicated in Article 8(2) of the ECHR (prevention of and fight against serious crime, protection of general security, national security). Therefore, the question arises as to when the procedural authorities may obtain location data (what offences may justify interference with the right to privacy) and what conditions should be met by national law with regard to this issue.  The ECtHR and the CJEU are increasingly dealing with cases that concern the collection of location data in real time and data retention by telecommunications service providers. This requires an assessment of whether a European standard has now been developed and, if so, what is the standard?